Advertising strategy and its effectiveness on consumer online search in a defaming product-harm crisis. Issue 3 (11th June 2018) - Jang, Sungha; Kim, Jinsoo; Song, Reo; Kim, Ho
Abstract : Purpose: Actual product-harm crises pose significant challenges to firms, but so can defaming product-harm crises, which are defined as crises caused by false or malicious rumors made by consumers or competing firms. Unlike typical product-harm crises, in defaming product-harm crises, the truth often emerges only after substantial damage has been done to the victim firm. Thus, crisis management strategies in these two cases may be different. The paper aims to discuss these issues. Design/methodology/approach: Using a defaming product-harm crisis that involved two competing firms, this paper examines how the firms changed their advertising strategies and how the changes affected consumers' online search behavior regarding the two firms. Findings: The analyses show that after the crisis, the offending firm sensitively reacted to its own and the victim firm's advertising levels, but the victim firm did not react to the offending firm's advertising as it had previously. The effectiveness of advertising on consumers' online search weakened for both firms after the crisis. Originality/value: The paper provides a new insight about marketing strategies and their effectiveness in the product-harm crisis literature.